1996
DOI: 10.1002/(sici)1097-0363(19961215)23:11<1133::aid-fld456>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of Wall-Bounded Complex Flows and Free Shear Flows

Abstract: Various wall‐bounded flows with complex geometries and free shear flows have been studied with a newly developed realizable Reynolds stress algebraic equation model. The model development is based on the invariant theory in continuum mechanics. This theory enables us to formulate a general constitutive relation for the Reynolds stresses. Pope (J. Fluid Mech., 72, 331–340 (1975)) was the first to introduce this kind of constitutive relation to turbulence modelling. In our study, realizability is imposed on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 13 publications
0
32
0
1
Order By: Relevance
“…turbulence model equation should obey [12]. The realizability inequalities for 3D turbulent flows are as follows:…”
Section: Consideration Of Realizability For Plane Shear Layermentioning
confidence: 99%
“…turbulence model equation should obey [12]. The realizability inequalities for 3D turbulent flows are as follows:…”
Section: Consideration Of Realizability For Plane Shear Layermentioning
confidence: 99%
“…In this work, a model developed by Shih et al (1996) is used, which relates the mean strain rate of the flow to the Reynolds stress tensor through the algebraic nonlinear Reynolds stress model. The model adjusts the Reynolds stress, τ, by adding a nonlinear stress term τ NL , defined as…”
Section: Nonlinear (Nl)mentioning
confidence: 99%
“…Shih et al (1996) showed the nonlinear k − ǫ model performs better than the standard k − ǫ model under strong adverse pressure gradients, as well as for separated and swirling flows.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…is calculated with a nonlinear eddy viscosity relationship suggested by Shih et al 1996. This nonlinear closure relationship for Reynolds stress mimics the more complete Reynolds-stress closure without solving the transport equations of Reynolds stress.…”
Section: Numerical Modelmentioning
confidence: 99%